Photoperiod and Temperature as Dominant Environmental Drivers Triggering Plant Phenological Development of American Ginseng Along With Its Quality Formation - Chen, Tingting; Wang, Liqin; Wang, Hongtao; Jiang, Sheng; Zhou, San (Frontiers in Earth Science, 2022)
American ginseng (Panax quinquefolius L.) has been cultivated in many locations in China, and we have noticed that its phenological performance and quality characteristics varied from location to location. However, the exogenous factors driving this process are still poorly understood, and this reduces the successful introduction of American ginseng for quality ensuring. Here, we conducted field and cabinet experiments to explore the relationship among environmental factors, phenological development, and ginsenoside accumulation in American ginseng. In the field experiments, we found that American ginseng from different original locations showed different phenological rhythms and different ginsenoside accumulation. Especially, those from higher latitude locations (e.g., Wuchang, 44.55°N) presented delayed spring phenology and advanced autumn phenology, but higher ginsenoside contents along with higher gene expression levels of ginsenoside biosynthesis than those from lower latitude locations (e.g., Wendeng, 37.23°N). Data analysis indicated that the phenological rhythm of American ginseng is closely related to the seasonal change in environmental factors, especially winter chilling duration, spring warming, and autumn day-length shortening. In the cabinet experiments, results further proved that temperature interaction with photoperiod plays a decisive role in the phenological development and ginsenoside accumulation of American ginseng in the absence of water and nutrient limitation. Both field and cabinet experiments indicated that sufficient winter cold exposure coupled with spring long day-length photoperiod is a beneficial environmental factor for normal spring phenology development, while shortening autumn day-length coupled with autumn cooling is a beneficial environmental factor for normal autumn phenology development of American ginseng. Results also indicated that insufficient cold exposure and unsuitable day-length photoperiod are detrimental factors to both spring and autumn phenology, and are not good for ginsenoside accumulation in American ginseng. An understanding of the environmental factors influencing phenological development along with ginsenoside accumulation can provide guidance for predicting suitable cultivation locations and improving planting techniques for high yield and good quality of American ginseng.